Pride and prejudice - Jane Austen; James Kinsley (Oxford University Press, 2004)
Pride and Prejudice has delighted generations of readers with its unforgettable cast of characters, carefully choreographed plot, and a hugely entertaining view of the world and its absurdities. With the arrival of eligible young men in their neighborhood, the lives of Mr. and Mrs. Bennet and their five daughters are turned inside out and upside down. Pride encounters prejudice, upward-mobility confronts social disdain, and quick-wittedness challenges sagacity, as misconceptions and hasty judgements lead to heartache and scandal, but eventually to true understanding, self-knowledge, and love